Implementasi Metode Sorogan dalam Meningkatkan Pemahaman Kitab Fathul Qarib di Asrama Al Umamy Pondok Pesantren Nurul Huda Sukaraja, Buay Madang, OKU Timur Tahun 2022 - Hasyim, Muhammad; Sodikin, Ahmad (Prodi Pendidikan Agama Islam, 2022)
The sorogan method is a method that is carried out by way of the santri one by one coming to the kyai who will read several lines of Arabic books and interpret them into a certain language, then the students repeat and translate or in terms of pesantren often called murodi. The research is still using a qualitative approach. The method used in this research is the method of observation, interview method and method of documentation. The findings of the researcher are (a) The process of implementing the learning has been going well and smoothly. (b) The supporting factor is that teachers are more able to supervise and guide students directly, students will more easily master the contents of the book and Arabic grammar. While the inhibiting factors are the lack of teachers, spending a lot of time, the occurrence of frequent conflicts between the busy hours of the teacher and the learning hours of the students, the sorogan method is considered inefficient because the teacher only handles one student, and most importantly the lack of discipline problems.